Effect of Yoga Physical Activity on Increasing Self-Control and Quality of Life - Rahayu, Nur Indri; Amalia, Triska Pangestu; Damayanti, Imas (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
The purpose of this study was to determine the effect of physical activity of yoga on improving self-control and quality of life. The method used is experimental with The One-Group Pretest-Posttest Design research design. The sample of this research is the active female students of UPI Sport Science with a total sample of 28 people. The sampling technique uses purposive sampling. The instrument used was an adaptation of the Self-Control Scale questionnaire to test the increase in self-control and WHOQOL-100 to test the increase in quality of life. Data analysis used was Paired Sample t-Test to test the effect of yoga physical activity on increasing self-control and quality of life. The results of data analysis showed that there was an influence of physical activity of yoga on the increase in self-control (Z = -3,343, p = 0.001) and quality of life (t = -3.663, p = 0.001). So, it can be concluded that there is an influence of physical activity of yoga on increasing self-control and quality of life.